Loneliness and lack of belonging as paramount theme in identity descriptions of Children Born of War - Mitreuter, Saskia; Glaesmer, Heide; Kuwert, Philipp; Kaiser, Marie (Frontiers in Political Science, 2022)
Objective Children Born of War (CBOW) are an international and timeless phenomenon that exists in every country involved in war or armed conflict. Nevertheless, little is known on a systematic level about those children, who are typically fathered by a foreign or enemy soldier and born to a local mother. In particular, the identity issues that CBOW often report have remained largely uninvestigated. In the current qualitative study we began filling this gap in the scientific literature by asking how CBOW construct their identity in self-descriptions. Method We utilized thematic content analysis of N = 122 German CBOWs' answers to an open-ended questionnaire item asking how they see themselves and their identity in the context of being a CBOW. Results We identified five key themes in CBOW' identity accounts. Loneliness and lack of belonging appeared as a paramount aspect of their self-descriptions next to narratives about belonging and positive relationship. On a less interpersonal basis, we found fighting and surviving and searching for truth and completion overarching aspects of their identities. There were also few accounts growing up unaffected by the fact of being born a CBOW. Although all themes portray different perspectives, they all (but the last one) clearly indicate the impeded circumstances under which CBOW had to grow up. Conclusions Integrating our findings with existing interdisciplinary literature regarding identity, we discuss implications for future research and clinical and political practice.